Etching of graphene on Ir(111) with molecular oxygen. (January 2016) - Schröder, Ulrike A.; Grånäs, Elin; Gerber, Timm; Arman, Mohammad A.; Martínez-Galera, Antonio J.; Schulte, Karina; Andersen, Jesper N.; Knudsen, Jan; Michely, Thomas
Abstract: The mechanisms for oxygen etching of graphene on Ir(111) are uncovered through a systematic variation of the graphene morphology – ranging from an impermeable graphene layer to graphene nanoflakes – and the application of complementary experimental methods, including scanning tunneling microscopy, X-ray photoelectron spectroscopy, and temperature programmed desorption. Associated with a strong variation in the onset temperature for etching, we find a fundamental difference in the onset of etching for an impermeable layer and for graphene flakes. For the impermeable graphene layer etching is shown to nucleate at graphene pentagon–heptagon point defects through molecules impinging from the gas phase. For graphene flakes the nucleation problem is absent due to the existence of edges in contact with the metallic substrate. The substrate enables dissociative chemisorption of oxygen, which can then diffuse as atomic oxygen to the graphene edge. Our results show that intercalation of oxygen is neither a necessary condition nor of specific relevance for etching. Based on our analysis, a quantitative estimate for the activation energy and attempt frequency of the elementary etch process in flake etching on Ir(111) is provided.